2022
DOI: 10.1002/pro.4393
|View full text |Cite
|
Sign up to set email alerts
|

Early divergence of translation initiation and elongation factors

Abstract: Protein translation is a foundational attribute of all living cells. The translation function carried out by the ribosome critically depends on an assortment of protein interaction partners, collectively referred to as the translation machinery. Various studies suggest that the diversification of the translation machinery occurred prior to the last universal common ancestor, yet it is unclear whether the predecessors of the extant translation machinery factors were functionally distinct from their modern count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Taken together, the LUCA appears to represent a population of organisms with many of the molecular systems that are seen in extant life, including protein-mediated metabolism ( 39 , 40 ), cellular organization ( 41 , 42 ), and a genetic system consisting of a DNA genome ( 43 45 ), RNA transcripts ( 46 ), the translation machinery ( 47 52 ), and the canonical genetic code ( 53 56 ). Given the results of proteome reconstructions and other phylogenetic analyses of ancient protein families, the LUCA appears to represent a stage in evolution well past the origin of life ( 36 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the LUCA appears to represent a population of organisms with many of the molecular systems that are seen in extant life, including protein-mediated metabolism ( 39 , 40 ), cellular organization ( 41 , 42 ), and a genetic system consisting of a DNA genome ( 43 45 ), RNA transcripts ( 46 ), the translation machinery ( 47 52 ), and the canonical genetic code ( 53 56 ). Given the results of proteome reconstructions and other phylogenetic analyses of ancient protein families, the LUCA appears to represent a stage in evolution well past the origin of life ( 36 ).…”
mentioning
confidence: 99%
“…The branch connecting these LUCA nodes, therefore, represents an evolutionary event prior to the LUCA. Most of these universal paralog families are components of the translation system, e.g., the family containing the translation regulatory proteins Elongation Factor tu, Elongation Factor G, and Initiation Factor ( 47 ), as well as several families of aminoacyl transfer ribonucleic acid synthetases ( 48 , 49 ). Other universal paralog families encode proteins with membrane-related functions such as the SRP membrane targeting system ( 59 ), subunits of the adenosine triphosphate (ATP) synthase complex ( 60 ), and membrane-spanning ATP-binding cassette transporter (ABC-transporters) ( 58 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and yet remains tightly coupled to the host translation machinery and physiology [61][62][63][64][65]. Intriguingly, while the evolutionary origin of IF2 is less well known, several paths have been proposed for the diversification of elongation and initiation factors from a single ancestor at the time of LUCA [59,60,[66][67][68]. Recently, reconstruction of IF2/EF-Tu ancestry suggested that the common ancestor of IF2/EF-Tu exhibits characteristics of both IF2 and EF-Tu and evolved specialized functions after gene duplication [67].…”
Section: Translation Factorsmentioning
confidence: 99%
“…The relative simplicity of life forms at the origin compared to the relative complexity of life at the time of the LUCA suggests that many of the most foundational characteristics of life emerged during these most early stages in evolution. These include cellular organization (Harris & Goldman, 2021; Koonin, 2014), protein‐mediated metabolism (Caetano‐Anollés et al, 2009; Goldman et al, 2016), and the tripartite genetic system consisting of the DNA genome (Goldman & Landweber, 2012; Nagel & Doolittle, 1995; Poole et al, 2014), RNA transcripts (Hoeppner et al, 2012), the translation machinery (Fer et al, 2022; Fournier et al, 2011; Mushegian, 2008; Petrov et al, 2015; Woese, 1998) and the genetic code (Crick, 1968; Knight et al, 1999; Trifonov, 2000; Woese, 1965).…”
Section: Introductionmentioning
confidence: 99%